2015
DOI: 10.1063/1.4918761
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical screening of van der Waals interactions in nanostructured solids: Sublimation of fullerenes

Abstract: Sublimation energy is one of the most important properties of molecular crystals, but it is difficult to study, because the attractive long-range van der Waals (vdW) interaction plays an important role. Here, we apply efficient semilocal density functional theory (DFT), corrected with the dynamically screened vdW interaction (DFT + vdW), the Rutgers-Chalmers nonlocal vdW-DF, and the pairwise-based dispersion-corrected DFT-D2 developed by Grimme and co-workers, to study the sublimation of fullerenes. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…However, semilocal DFT often fails to describe this process, because the long-range vdW interaction is missing in semilocal DFT. Many attempts 25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54] have been made to capture this long-range part, such as nonlocal vdW-DF functional 41 and density functional dispersion correction 55,56 . It has been shown that with a proper dispersion correction, the performance of ordinary DFT methods can be significantly improved 26 .…”
Section: Vdw Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, semilocal DFT often fails to describe this process, because the long-range vdW interaction is missing in semilocal DFT. Many attempts 25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54] have been made to capture this long-range part, such as nonlocal vdW-DF functional 41 and density functional dispersion correction 55,56 . It has been shown that with a proper dispersion correction, the performance of ordinary DFT methods can be significantly improved 26 .…”
Section: Vdw Coefficientsmentioning
confidence: 99%
“…This model was modified by Breckenridge, Shaw, and Sher to satisfy the Kramers-Kronig relation 23 . The modified Penn model has been used to calculate the vdW coefficient C 3 for the adsorption of atoms on surfaces 24 and the dielectric screening effect for the vdW interaction in solids 25 . In particular, Tao and Rappe 26 have recently applied the frequency-dependent model dielectric function and a simple yet accurate model dynamic multipole polarizability to calculate the leading-order as well as higher-order vdW coefficients C 3 and C 5 for atoms on a variety of solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…When R at equilibrium is not so large, in particular, for densely packed solids, C 8 and C 10 terms can be as large as C 6 term. 9 Clearly, a vdW correction based on the leading-order coefficient C 6 alone is not sufficient to provide adequate description of the long-range vdW interaction in many molecular solids. Inclusion of higher-order contributions is important for achieving systematic improvement of the vdW correction even within sophisticated pairwise models.…”
mentioning
confidence: 99%
“…As a result, it often fails to describe the intermolecular interaction and phenomena arising from it (e.g., sublimation and physisorption). It has been shown that a proper vdW correction can significantly improve the performance of conventional DFT, greatly extending its applicability to a broader class of problems such as molecular complexes and solids [2][3][4][5][6][7][8][9] and layered materials. 10,11 The vdW interaction is an important long-range nonlocal correlation arising from instantaneous charge fluctuations on each density fragment.…”
mentioning
confidence: 99%
“…The first property is very important for surface energy calculations, while the second is helpful in capturing the van der Waals interactions, [72][73][74][75][76][77][78][79] as demonstrated by the excellent performance of the TM functional for lattice constants (Table II) and cohesive energies (Table V). Recently, we have also assessed 80 the TM functional on diverse molecular properties and found that it has a similarly good accuracy for atoms and molecules as for solids.…”
Section: Discussionmentioning
confidence: 99%